2014
DOI: 10.1055/s-0033-1338598
|View full text |Cite
|
Sign up to set email alerts
|

Cheap and Easy Synthesis of Highly Functionalized (Het)aryl Iodides via the Aromatic Finkelstein Reaction

Abstract: Aryl iodides are superior coupling partners in crosscoupling reactions compared to the corresponding chlorides or bromides. Unfortunately, the iodides are much more expensive, if commercially available at all, than the other halides. Thus, it is often mandatory to transform the available bromides into the corresponding iodides. The copper-catalyzed aromatic Finkelstein reaction turned out to be the method of choice to prepare a number of highly functionalized iodo(het)aryls, including pyridines, 2,2′-bipyridin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Firstly, the rate at which equilibrium is reached usually requires less than eight hours which, by contrast, is dramatically faster than the 22 and 40 hours characteristic of prior conversions (Scheme 9). 2,3,11,[20][21][22] Also noteworthy is that the catalyst/solvent system developed accommodates important substrate functionality. Thus, in addition to increased tolerance of sensitive functional groups as documented in the Schemes shown earlier, as well as in Scheme 8, substrates bearing free O-H groups can now readily participate, unlike previous approaches that required considerable manipulation of the hydroxy group.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the rate at which equilibrium is reached usually requires less than eight hours which, by contrast, is dramatically faster than the 22 and 40 hours characteristic of prior conversions (Scheme 9). 2,3,11,[20][21][22] Also noteworthy is that the catalyst/solvent system developed accommodates important substrate functionality. Thus, in addition to increased tolerance of sensitive functional groups as documented in the Schemes shown earlier, as well as in Scheme 8, substrates bearing free O-H groups can now readily participate, unlike previous approaches that required considerable manipulation of the hydroxy group.…”
Section: Resultsmentioning
confidence: 99%
“…The scope of the reaction was shown to be remarkably broad and this process clearly is one of the most efficient to date, as exemplified with representative synthetic application of this process that will be overviewed in section Synthetic Applications of Halogen Exchanges in Aryl Halides and its use in natural product synthesis (Fürstner and Kennedy, 2006 ; Carr et al, 2010 ). It was later on extended to other (hetero)aryl bromides (Lützen et al, 2014 ) and to continuous flow chemistry using a sodium iodide packed-bed reactor (Chen et al, 2014 ) and recent studies demonstrated that the reaction time could be shortened using microwave irradiation (Cannon et al, 2011 ) and that other diamines and some triamines (Jin and Davies, 2017 ) could also be used as ligands. Aryl chlorides are in general poor substrates in this reaction.…”
Section: Halogen Exchange In Aryl Halidesmentioning
confidence: 99%
“…After Boc protection of the amino group of 4 , the aromatic Finkelstein reaction was performed to obtain a more reactive iodine intermediate. 7 This allowed us to carry out further Suzuki–Miyaura cross-coupling at lower temperature (60 °C) and then avoid reaction at the halogen position of the product 8 2-bromophenyl group. However, despite numerous attempts, we found that halogen exchange remained incomplete (~2:1 I/Br ratio from 6 ).…”
mentioning
confidence: 99%